2016
DOI: 10.3390/cosmetics3030025
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Statistical Evaluation of Serious Undesirable Effects of Cosmetic Products in the EU

Abstract: The Council of Europe created an outline for a vigilant system of undesirable effects of cosmetic products in 2006. In 2013, some of those aspects were included in the European Cosmetics Regulation (EC) 1223/2009. Since then, serious undesirable effects (SUEs), which are the tip of the iceberg of all undesirable effects of cosmetic products, have to be reported to competent authorities. Neglecting the first phase of establishing the system, we have about two years of experience regarding the notification of SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
6
0
3
Order By: Relevance
“…Since 2013, cosmetic companies are obliged to notify all reported SUEs, except those with causality assessment "excluded" to the competent Authorities. The first statistical analysis of SUEs reported in the European Union (2014-2015) showed that hair-colouring and skin-care products stand out regarding the number of cases and the seriousness criterion leading to hospitalization [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, cosmetic companies are obliged to notify all reported SUEs, except those with causality assessment "excluded" to the competent Authorities. The first statistical analysis of SUEs reported in the European Union (2014-2015) showed that hair-colouring and skin-care products stand out regarding the number of cases and the seriousness criterion leading to hospitalization [16].…”
Section: Discussionmentioning
confidence: 99%
“…u frizerskom salonu. U 74% svih slučajeva povezanost između izlaganja kozmetičkom proizvodu i pojave ozbiljnih neželjenih efekata se pokazala "verovatnom" ili "vrlo verovatnom" [15]. U najvećem broju slučajeva posledice su bile privremena sprečenost za rad, u 26% slučajeva bila je neophodna hospitalizacija, npr.…”
Section: Kozmetički Proizvodi Kao Uzročnici Pojave Ozbiljnih Neželjenunclassified
“…Registrovana su dva smrtna slučaja, po jedan nakon primene farbe za kosu i proizvoda za negu kože. U pogledu identifikovanih SUEs većinom su bili prijavljeni kontaktni alergijski dermatitisi (34,4%) ili iritacija kože (3,8%), dok se u 6,3% slučajeva radilo o sistemskom efektu i pojavi anafilaktičkog šoka [15]. Autori ističu da je malo ovih reakcija potvrđeno od strane medicinskog osoblja, te je moguća prijava i lažnih reakcija.…”
Section: Kozmetički Proizvodi Kao Uzročnici Pojave Ozbiljnih Neželjenunclassified
See 1 more Smart Citation
“…The statistics also found that hair dyes skin care products were most commonly implicated in SUEs. 9 In retrospective study conducted over a period of 5 years in the Netherlands reported itching (70.9%), burning sensation (50%), and dryness of skin (63.3%) as the most common adverse events. 10 Dermatitis caused by kumkum and hair dye is prevalent in India.…”
mentioning
confidence: 99%